Meningkatkan Kemampuan Menulis Karangan Naratif Menggunakan Model Pembelajaran Kooperaif Tipe Pengaliran Program IMAS ( Image Streaming) Siswa Kelas IV MIN 6 Cilacap - Tasikin Tasikin (JRPD (Jurnal Riset Pendidikan Dasar), 2021)
This classroom action research aims to improve the ability to write narrative through the IMAS (image streaming) learning model in class IV MIN 6 Cilacap, which amounts to 29 students. The data collection techniques used were observation, documentation and test models. The data analysis technique used is a descriptive analysis model to measure the ability to write the results of research tests (1 time giving the test) in each cycle using frequency distribution and the first percentage that there is an increase in the quality of the learning process to write narrative paragraphs after class action is held with the IMAS learning model ( Image Streaming). The results showed an increase in student learning outcomes. The average score of 69.59 cycle I with classical completeness 16 people (55.17%) complete, is in the low category and increases in cycle II 83.13 with classical completeness 29 people (100%) complete. This is supported by the increased activity and creativity of students in the teaching and learning process from cycle I to increase in cycle II. This means that the application of the IMAS (Image Streaming) learning model in Indonesian language learning can improve the ability to write narrative paragraphs for grade IV students of MIN 6 Cilacap.